E-001 Partial central retinal artery occlusion following para-ophthalmic artery embolization: a case report. (12th July 2011) - Chowdhry, S; Sharma, J; Blackham, K
Abstract : Background: Coil embolization of para-ophthalmic artery aneurysms can result in acute as well as delayed visual complications. Progressive visual changes have been have been ascribed to mass effect from aneurysm thrombosis or peri-aneurysmal inflammation or edema. Abrupt, fixed visual changes are likely secondary to thromboembolic complications which result in retinal infarcts via the ophthalmic artery. Although thromboembolic complications are well described in general, clinical reports of retinal infarcts following coil embolization are rare in the literature. Thromboembolic complications resulting in central or branch retinal artery occlusion may occur in a delayed fashion following the coiling procedure. Case Report: A 43-year-old woman presented for elective coil embolization of an unruptured right para-ophthalmic artery aneurysm, measuring 7 by 7 mm with a 4 mm neck and projecting superiorly. The origin of the ophthalmic artery was located immediately inferomedial to the neck of the aneurysm. The embolization procedure was uneventful and accomplished with stent-assisted coiling utilizing predominantly Cerecyte coils. Systemic heparinization was used during the procedure, and Plavix was administered both 7 days before the procedure and continued after the procedure. About 12 h following the procedure she complained of right-sided positive visual phenomena followed by a headache. She was found to have a visual field defect OD but it was felt that the visual loss was most likely secondary to compressive optic neuropathy and she was discharged home on oral steroids. She returned to clinic 4 days later stating that her vision was not improving. Ophthalmologic exam revealed dense nasal and central defects OD, and full fields OS. Extensive areas of retinal infarction OD were seen on dilated fundus exam with the suggestion of subtle platelet-fibrin emboli. It was felt that the cause was likely artery-to-artery embolism resulting in partial central retinal artery occlusion following the coiling procedure. Vasospasm was considered but felt to be less likely. The symptoms did not resolve with oral verapamil and timolol eye drops. Conclusion: Our case highlights the rare but potential complication of central or branch retinal artery occlusion from the endovascular treatment of para-ophthalmic artery aneurysms. Along with mass effect from aneurysm thrombosis or peri-aneurysmal edema, it remains an uncommon but serious cause of morbidity in these patients.